Muslim consumers’ behaviour towards halal nutraceutical products in Malaysia - Siti Nurunnajwa, S.; Elistina, A.B.; Syuhaily, O.; Nuradli Ridzwan Shah, M.D. (Rynnye Lyan Resources, 2024)
Nutraceutical is defined as a food, or parts of a food, that provide medical or health benefits, including disease prevention and treatment. Although the primary source of nutraceutical products is plant-based, not all nutraceutical products can be categorized as halal. Many ingredients are involved in food processing and used as flavours, stabilizers, or colouring agents. In addition, some additives may be derived from non-halal sources, whether from pork, blood, non-slaughtered animals, genetically modified, or extracted with ethanol. Therefore, there is a need to identify the factors influencing Muslims’ consumer behaviour towards halal nutraceutical products to improve their awareness of them in Malaysia. For this reason, the present study has been developed to examine the factors that affect Muslim behaviour in purchasing halal nutraceutical products. This study employed a quantitative approach, with a total of 400 Muslim consumers in Malaysia participating and selected through multi-stage random sampling. Multiple regression analysis was used to determine whether Islamic values, religiosity, the maqasid shariah principle, and trust in government influence consumer behaviour toward halal nutraceutical products. The result indicated that all four factors significantly affect the consumers’ behaviour, where trust in the government was the most substantial predictive factor. This study was expected to improve halal awareness among Muslim consumers while encouraging the government to strengthen the Halal industry to protect the welfare of Muslim consumers in Malaysia.